Surface Wave Reduction in Antenna Arrays Using Metasurface Inclusion for MIMO and SAR Systems. Issue 11 (21st November 2019) - Alibakhshikenari, Mohammad; Virdee, Bal S.; See, Chan H.; Abd‐Alhameed, Raed A.; Falcone, Francisco; Limiti, Ernesto
Abstract: An effective method is presented for suppressing mutual coupling between adjacent radiating elements which is based on metasurface isolation for multiple‐input multiple‐output (MIMO) and synthetic aperture radar (SAR) systems. This is achieved by choking surface current waves induced over the patch antenna by inserting a cross‐shaped metasurface structure between the radiating elements. Each arm of the cross‐shaped structure constituting the metasurface is etched with meander line slot. Effectiveness of the metasurface is demonstrated for a 2 × 2 antenna array that operates over six frequency subbands in X, Ku, and K bands. With the proposed technique, the maximum improvement achieved in attenuating mutual coupling between neighboring antennas is 8.5 dB (8–8.4 GHz), 28 dB (9.6–10.8 GHz), 27 dB (11.7–12.6 GHz), 7.5 dB (13.4–14.2 GHz), 13 dB (16.5–16.8 GHz), and 22.5 dB (18.5–20.3 GHz). Furthermore, with the proposed technique (i) minimum center‐to‐center separation between the radiating elements can be reduced to 0.26 λ 0, where λ 0 is 8.0 GHz; (ii) use of ground‐plane or defected ground structures are unnecessary; (iii) use of short‐circuited via‐holes are avoided; (iv) it eliminates the issue with poor front‐to‐back ratio; and (v) it can be applied to existing arrays retrospectively. Key Points: An effective method is presented for mutual coupling reduction that is based on metasurface isolator for MIMO and SAR applications Effectiveness of the metasurface is demonstrated with a 2x2 antenna array that operates over six frequency sub‐bands in X, Ku and K‐bands The maximum improvement achieved in attenuating mutual coupling is 8.5, 28, 27, 7.5, 13, and 22.5 dB at six frequency bands, respectively